2006
DOI: 10.1097/01.mlg.0000224368.58870.3c
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Metalloprotease Inducer Stimulates Fibroblast‐Mediated Tumor Growth In Vivo

Abstract: As a cell surface expressed protein that promotes tumor growth and high expression in head and neck squamous cell carcinoma but not in normal tissue, EMMPRIN may be a good target for directed molecular therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In this latter study, co-cultures of SKG-II cells and fibroblasts exhibited increased in vitro invasive activity of SKG-II cells via increased activation of fibroblast-derived proMMP-2 on the tumor cell surface. Promotion of tumorigenesis by co-injection of emmprin-expressing tumor cells and dermal fibroblasts was also reported (39). In our study, emp#2 peptide inhibited not only emmprin-mediated MMP-2 upregulation, but also the glioblastoma cell invasion augmented by interacting with fibroblasts.…”
Section: Discussionsupporting
confidence: 54%
“…In this latter study, co-cultures of SKG-II cells and fibroblasts exhibited increased in vitro invasive activity of SKG-II cells via increased activation of fibroblast-derived proMMP-2 on the tumor cell surface. Promotion of tumorigenesis by co-injection of emmprin-expressing tumor cells and dermal fibroblasts was also reported (39). In our study, emp#2 peptide inhibited not only emmprin-mediated MMP-2 upregulation, but also the glioblastoma cell invasion augmented by interacting with fibroblasts.…”
Section: Discussionsupporting
confidence: 54%
“…Cells were incubated at 37°C in a humidified atmosphere containing 5% CO 2 . Human umbilical vein endothelial cells (University of Alabama at Birmingham) were maintained in M199 media with 0.1 g/L heparin, 0.1 g/L endothelial cell growth factor, and 10% fetal bovine serum with antibiotics, as previously described (13). Normal dermal fibroblast isolation from primary culture and construction of the FaDu/siE cell lines by siRNA knockdown were also as described previously (13, 22).…”
Section: Methodsmentioning
confidence: 99%
“…Collagen assays were done as previously described (13) using type I collagen (BD Biosciences). FaDu, FaDu/siE, and normal dermal fibroblast cells were plated in 25 μL of DMEM with 0.1% bovine serum albumin in the center of each well and allowed to adhere for 2 h. Additional media with or without anti-EMMPRIN mAb, CNTO3899, was added to each well, and cells were incubated for 4 d. At the end of treatment, cells were removed and wells were stained with Coomassie blue (0.2%).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in breast cancer, increased EMMPRIN expression results in immediate stimulation of VEGF and MMP production in tumor and stromal cells, and tumor-derived MMP can increase soluble VEGF or release biologically active angiogenic growth factors from matrix-bound complexes to modulate VEGF secretion in an MMP-dependent fashion in vivo. 26,[49][50][51] Recent findings also illustrate that EMMPRIN stimulates fibroblast-mediated tumor growth in head and neck squamous cell carcinoma in vivo, 52 and revealed that fibroblasts have a more profound influence on the development and progression of carcinomas.…”
Section: Discussionmentioning
confidence: 99%